Calcium Consumption During Pregnancy: A Multicenter Study in a Middle-Income Country in Southeast Asia - Panburana P; Komwilaisak R; Tongprasert F; Phadungkiatwattana P; Kor-anantakul O; Lumbiganon P (Dove Medical Press, 2021)
Panyu Panburana,1 Ratana Komwilaisak,2 Fuanglada Tongprasert,3 Podjanee Phadungkiatwattana,4 Ounjai Kor-anantakul,5 Pisake Lumbiganon2 1Department of Obstetrics & Gynecology, Faculty of Medicine, Ramathibodi University Hospital, Mahidol University, Bangkok, Thailand; 2Department of Obstetrics & Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 3Department of Obstetrics & Gynecology, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 4Rajavithi Hospital, Ministry of Public Health, Bangkok, Thailand; 5Department of Obstetrics & Gynecology, Faculty of Medicine, Songklanagarind Hospital, Prince of Songkla University, Hat Yai, Songkhla, ThailandCorrespondence: Panyu PanburanaDepartment of Obstetrics & Gynecology, Faculty of Medicine, Ramathibodi University Hospital, Mahidol University, Bangkok, ThailandEmail ppanburana@yahoo.comObjective: To perform a cross-sectional observational study of calcium consumption among pregnant women from multicenter tertiary care hospitals in the middle-income country in Southeast Asia.Study Design: A cross-sectional observational study.Setting: The study was conducted in four geographical regions (northern, northeastern, southern, and central) of Thailand. Five participating hospitals consisted of one university hospital in each region and one additional tertiary care hospital in the central region.Materials and Methods: A cross-sectional study was performed nationwide from 1st November 2017 to 31st January 2019. All singleton aged 19– 40 years were included. Exclusion criteria were any conditions that influenced calcium-containing food consumption. Dietary intake self-records immediately after eating for two working days and one holiday were analyzed via INMUCAL-NV3.0 dietary program.Results: The 1549 records were obtained. The mean age was 29 ± 5.7 years. Most participants were primigravida (48.6%). The average gestational age was 20.6 ± 8.8 weeks. Mean calcium consumption was 602.4 mg/day (95% CI; 589.2615.6 mg/day) mg/dL. Inadequate calcium consumption prevalence based on the Thai dietary reference intake (less than 800 mg/day) and US Institute of Medicine (less than 1000 mg/day) were 82.0% and 93.4%, respectively.Conclusion: The mean calcium consumption among pregnant women in the middle-income country in Southeast Asia was 602.4 mg/day (95% CI 589.2– 615.6 mg/day). Inadequate calcium consumption of Thai pregnant women prevalence was 82.0% and 93.4% according to Thai dietary reference intake in pregnancy and the US Institute of Medicine.Keywords: calcium consumption, pregnancy, a middle-income country, Southeast Asia